2016
DOI: 10.1021/acs.chemmater.6b04086
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Interfacial Chemistry of Organic Electrodes in Li- and Na-Ion Batteries

Abstract: Organic compounds are increasingly being investigated as electrode materials for Li-or Na-ion batteries. Even though their gravimetric capacity can challenge that of their inorganic counterparts, a number of problems need further attention, not least their chemical and electrochemical stability toward the electrolyte systems. There has been speculation that several of these issues have their origin in the formation of a less stable solid electrolyte interphase (SEI) layer and its evolution during battery cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…Additionally, the Na‐based SEI eschewed the long (CH 2 ) x  hydrocarbon chains found in the Li‐based SEI, instead of favoring carbonates, and other‐CO rich species, which could explain for the formation of a thicker, and more homogeneous SEI layer. A later study by Brandell and co‐workers confirmed the findings of the thicker, more homogenous SEI layer, showing that the Na SEI contains a significantly higher content of inorganic components, as compared to the Li‐based SEI, which has a higher concentration of organic components . This suggests two things: first, that the Li‐based environment is less reactive, as the SEI is still composed of organic solvent molecules.…”
Section: Seimentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, the Na‐based SEI eschewed the long (CH 2 ) x  hydrocarbon chains found in the Li‐based SEI, instead of favoring carbonates, and other‐CO rich species, which could explain for the formation of a thicker, and more homogeneous SEI layer. A later study by Brandell and co‐workers confirmed the findings of the thicker, more homogenous SEI layer, showing that the Na SEI contains a significantly higher content of inorganic components, as compared to the Li‐based SEI, which has a higher concentration of organic components . This suggests two things: first, that the Li‐based environment is less reactive, as the SEI is still composed of organic solvent molecules.…”
Section: Seimentioning
confidence: 81%
“…A later study by Brandell and co-workers confirmed the findings of the thicker, more homogenous SEI layer, showing that the Na SEI contains a significantly higher content of inorganic components, as compared to the Li-based SEI, which has a higher concentration of organic components. [79] This suggests two things: first, that the Li-based environment is less reactive, as the SEI is still composed of organic solvent molecules. Additionally, it also suggests that the Na counter electrode used in the experiment may play an outsized role in the formation of the SEI, as side reactions between the Na counter electrode and the electrolyte would explain the shift towards a more inorganic SEI layer.…”
Section: Characterization and Comparisons With-li-based Seimentioning
confidence: 99%
“…Rechargeable lithium-ion batteries are now expected to put into use in hybrid electric vehicles (HEVs) and electric vehicles (EVs) [1] [2]. Unfortunately, the specific energy density of the present commercialized lithium-ion battery can hardly meet the requirements for practical applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…After 100 cycles, the Rct value remained stable at 402.7 Ω. From Figure S7, Supporting Information, the F1s peaks at NaF (684.2 eV), [43] TFSI (687.9 eV), and CÀ F 2 (688.9 eV) indicate that NaÀ F and NaÀ FÀ IL species are present. After 100 cycles, the Rct value remained stable at 551.2 Ω.…”
Section: Resultsmentioning
confidence: 96%